2015
DOI: 10.18632/oncotarget.6164
|View full text |Cite
|
Sign up to set email alerts
|

MiR-21-5p and miR-126a-3p levels in plasma and circulating angiogenic cells: relationship with type 2 diabetes complications

Abstract: Innovative biomarkers are required to manage type 2 diabetic patients (T2DM). We focused our study on miR-126-3p and miR-21-5p levels, as biomarkers of endothelial function and inflammation. MiRNAs levels were measured in plasma from 107 healthy subjects (CTR) and 193 diabetic patients (T2DM), 76 without (T2DM NC) and 117 with (T2DM C) complications.When diabetic complication were analysed as a whole, miR-126-3p and miR-21-5p levels declined significantly from CTR to T2DM NC and T2DM C patients. When miRNAs le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 46 publications
8
86
1
4
Order By: Relevance
“…The main characteristics extracted from various datasets are summarized in Table 1, which includes the number of patients investigated, the measurement platform, type of sample used and the identity of miRNAs in the study [23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81]. Comparing results from multiple tissues provides an overall view of the impact of miRNAs in T2DM pathology.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics extracted from various datasets are summarized in Table 1, which includes the number of patients investigated, the measurement platform, type of sample used and the identity of miRNAs in the study [23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81]. Comparing results from multiple tissues provides an overall view of the impact of miRNAs in T2DM pathology.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that knockout of miR-126 induces cardiac dysfunction [38, 39]. MiR-126 expression level in circulation is an indicator of systemic inflammatory and angiogenic status [40, 41]. MiR-126 concentration in the circulation is significantly decreased in ischemic stroke [17] and acute myocardial infarction patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, reduced levels of miR-21 in plasma and circulating cells were observed in patients affected by metabolic syndrome, T2DM and obesity (He et al, 2016; Zampetaki et al, 2010; Olivieri et al, 2015b; Mazloom et al, 2016). The reduced expression of miR-21 in circulating cells of obese subjects appears to be associated with an increased secretion of pro-inflammatory cytokines, and likely, it suggests a similar role in centenarians, who are also characterized by anti-inflammatory balancing processes (Franceschi et al, 2007).…”
Section: Circulating Mirs As Biomarkers Of Healthy and Unhealthy Amentioning
confidence: 95%